2022
DOI: 10.1002/cpdd.1185
|View full text |Cite
|
Sign up to set email alerts
|

Validation of an Announced Telephone Pill Count Compared to a Home‐Visit Pill Count in People With Type 2 Diabetes or Cardiovascular Disease

Abstract: We aimed to assess the validity of an announced telephone pill count in people with type 2 diabetes or cardiovascular disease by comparing this method to a home-visit pill count. We also assessed whether a second telephone pill count improved accuracy. People aged ≥35 years using oral type 2 diabetes or cardiovascular disease medication were included. Thirty-four participants completed a telephone pill count followed by a home-visit pill count, and a subsample of this population (n = 11) completed a second tel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
(97 reference statements)
0
0
0
Order By: Relevance
“…An alternative approach is a telephone-based pill count, where the patient self-reports their medication count while receiving guidance from a healthcare professional or researcher over the phone. Multiple studies have demonstrated that a telephone pill count can serve as a valid alternative to traditional home visit pill counts (59)(60)(61)(62). Pill count shares an assumption with MEMS -removal of a dosage unit equals medication intake.…”
Section: Pill Countmentioning
confidence: 99%
“…An alternative approach is a telephone-based pill count, where the patient self-reports their medication count while receiving guidance from a healthcare professional or researcher over the phone. Multiple studies have demonstrated that a telephone pill count can serve as a valid alternative to traditional home visit pill counts (59)(60)(61)(62). Pill count shares an assumption with MEMS -removal of a dosage unit equals medication intake.…”
Section: Pill Countmentioning
confidence: 99%